2006
DOI: 10.2190/9bf6-1kbl-y3cx-6qxg
|View full text |Cite
|
Sign up to set email alerts
|

Design, Development, and Validation of Learning Objects

Abstract: A learning object is a small, stand-alone, mediated content resource that can be reused in multiple instructional contexts. In this article, we describe our approach to design, develop, and validate Shareable Content Object Reference Model (SCORM) compliant learning objects for undergraduate computer science education. We discuss the advantages of a learning object approach, including positive student response and achievement, extension to other settings and populations, and benefits to the instructor and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…The finding of this study contributes to an understanding of engineering students' experiences, and opinion of undertaking technology in mathematics classes. The literature indicated the effectiveness of using technology as a learning tool to develop students' motivation and mathematics achievement (Ng & Gunstone, 2002;Nugent, Soh, & Samal, 2006;Shyu, 2000). However, the level of acceptance and competence in using these tools, fall largely upon the students and the instructors.…”
Section: Conclusion and Suggestionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding of this study contributes to an understanding of engineering students' experiences, and opinion of undertaking technology in mathematics classes. The literature indicated the effectiveness of using technology as a learning tool to develop students' motivation and mathematics achievement (Ng & Gunstone, 2002;Nugent, Soh, & Samal, 2006;Shyu, 2000). However, the level of acceptance and competence in using these tools, fall largely upon the students and the instructors.…”
Section: Conclusion and Suggestionmentioning
confidence: 99%
“…Even though, the ICT may promote educational change (Woodrow, 1987), the effective use of technology is truly dependent on the classroom teachers (NCTM, 2008) and how students can access to the new technologies and encourage to use them as learning tools. Several studies indicated that using technology effectively as a learning tool improves students' mathematics achievement and motivates students to learn mathematics and science (Tarmizi, Ayub & Bakar, 2008;Ng & Gunstone, 2002;Nugent, Soh, & Samal, 2006;Shyu, 2000). Further, it is important that students and teachers have suficient skills in productively using and working with ICT.…”
mentioning
confidence: 99%
“…Major strengths cited were reusability, ease of updates and content management, customization, interoperability, and overall flexibility. Research on LOs has also verified their instructional value [4,17].…”
Section: Technology-based Learning Platformsmentioning
confidence: 99%
“…Research has documented the instructional effectiveness of learning objects (Guy & LownesJackson, 2012;Kay, 2014;Nugent, Soh, & Samal, 2006;Tallmadge & Chitester, 2010) but little is known about their learning impact when used to meet different instructional objectives and when used in different learning contexts. The purpose of this study was to explore the learning impacts of learning objects packaged into online modules and used in different learning contexts.…”
Section: Introductionmentioning
confidence: 99%